Highly tenebrescent hackmanites from natural nepheline - Agamah, Cecilia; Vuori, Sami; Mäkilä, Ermei; Peuronen, Anssi; Lastusaari, Mika (Royal Society of Chemistry (RSC), 2025)
Photochromic hackmanites, (Na,K)8Al6Si6O24(Cl,S)2, were synthesized with a solid state reaction route using natural nepheline, (Na,K)AlSiO4, as a starting material together with NaCl, KCl and Na2SO4. The hackmanite was obtained using NaCl, whereas with KCl the nepheline reacted only partially. In particular, materials synthesized with NaCl showed a deep photochromic color under UV irradiation and good sensitivity to even low solar UV index values. This suggests that the material is well suited for personal solar UV exposure monitoring.